Development of live-attenuated arenavirus vaccines based on codon deoptimization of the viral glycoprotein - Cheng, Benson Y.H. (Virology, 2016)
Several arenaviruses, chiefly Lassa (LASV) in West Africa, cause hemorrhagic fever (HF) disease in humans and pose important public health problems in their endemic regions. To date, there are no FDA-approved arenavirus vaccines and current anti-arenaviral therapy is limited to the use of ribavirin that has very limited efficacy. In this work we dcument that a recombinant prototypic arenavirus lymphocytic choriomeningitis virus (LCMV) with a codon deoptimized (CD) surface glycoprotein (GP), rLCMV/CD, exhibited wild type (WT)-like growth properties in cultured cells despite barely detectable GP expression levels in rLCMV/CD-infected cells. Importantly, rLCMV/CD was highly attenuated in vivo but able to induce complete protection against a subsequent lethal challenge with rLCMV/WT. Our findings support the feasibility of implementing an arenavirus GP CD-based approach for the development of safe and effective live-attenuated vaccines (LAVs) to combat diseases caused by human pathogenic arenaviruses.